2017
DOI: 10.21541/apjes.297049
|View full text |Cite
|
Sign up to set email alerts
|

Yüksek Dayanımlı Betonla Üretilmiş Kirişlerde Plastik Mafsal Boyunun Belirlenmesi

Abstract: ÖzDepremler sırasında betonarme yapılar elastik olmayan deformasyonlar yaparak yapıya gelen enerjiyi sönümlerler. Yapılarda bulunan eğilme elemanlarında oluşan plastik deformasyonlar plastik mafsal bölgesi olarak adlandırılan küçük bir bölgede oluşur ve bu bölge elemanın yük taşıma ve deformasyon kapasitesi için kritik öneme sahiptir. Statik itme (Pushover) yöntemi mevcut yapıların değerlendirilmesinde kullanılan doğrusal olmayan bir analiz yöntemidir. Bu yöntemde elemanların plastik mafsal özelliklerinin doğr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For CDP two main failure mechanisms are tensile cracking and compressive crushing of the concrete [20]. The detail of the calculation of damage variable in compression and tension for this study can be found in [21]. The regular truss element in ABAQUS was employed for modeling of reinforcing bars.…”
Section: Preparation Of Numerical Modelmentioning
confidence: 99%
“…For CDP two main failure mechanisms are tensile cracking and compressive crushing of the concrete [20]. The detail of the calculation of damage variable in compression and tension for this study can be found in [21]. The regular truss element in ABAQUS was employed for modeling of reinforcing bars.…”
Section: Preparation Of Numerical Modelmentioning
confidence: 99%